Diagnostic Role of Colon Capsule Endoscopy in Patients with Optimal Colon Cleaning - Ümit Akyüz; Yusuf Yılmaz; Ali Tüzün İnce; Bülent Kaya; Cengiz Pata (Gastroenterology Research and Practice)
Background. Colon capsule endoscopy (CCE) is a diagnostic test with relatively rare usage. In this study, we aimed to evaluate both the optimal cleaning regimen for CCE and the diagnostic value of test in the study group. Methods. A total of 62 patients were enrolled in this study. In the first step, 3 different colon preparing regimens were given to 30 patients [Group A: 3 days of liquid diet, sodium phosphate (NaP) (90 mL), and NaP enema; Group B: 3 days of liquid diet, 4 L of polyethylene glycol (PEG), and metoclopramide; Group C: 3 days of liquid diet, 4 L of PEG, NaP (45 mL), and bisacodyl after capsule ingestion] (10 patients in each group). The other consecutive 32 patients were cleaned with the best regimen which was NaP + PEG and CCE was performed. The results of CCE were controlled with colonoscopy in 28 patients. Results. Group C had the highest cleaning score, compared with the other groups (2.2±0.4 versus 2.7±0.4 versus 3.7±0.4, p value =0.000). The CCE findings were as follows in 28 patients who were also examined with colonoscopy: polyp (range: 5–10 mm) in 6 patients, internal hemorrhoids in 3 patients, angiodysplasia in 1 patient, diverticula in 1 patient, and ulcerative colitis in 1 patient. The sensitivity, specificity, PPV, and NPV of CCE were 100%, 92%, 93%, and 100%, respectively. Conclusions. Low dosage NaP combined with PEG provides optimal bowel preparation for CCE. CCE appears to be a highly sensitive diagnostic modality for detecting colonic pathologies.